Asupan Gizi Makro dan Durasi Tidur pada Remaja Usia 16-18 Tahun dan Hubungannya terhadap Lama Menstruasi - Fauziah, Lilia Faridatul; Hanim, Diffah; Pamungkasari, Eti Poncorini (Media Kesehatan Masyarakat Indonesia, 2019)
Factors influence variations in adolescent menstrual duration would change the hormonal rhythm of the hypothalamic-pituitary-ovarian cycle, so that it indirectly changes the level of secretion of the reproductive hormones. Nutritional intake is predicted to be one of the factors in the regulation of reproductive hormones, as well as the sleep and wake cycles in a teenager. This study analyzed the relationship between macro nutrient intake and sleep duration with menstrual duration in adolescents aged 16-18 years. 120 adolescents was selected by using cluster random sampling from 6 high schools in Magelang City-Central Java for this cross sectional study. All of variable were collected through interview techniques using a questionnaire. Analysis with correlation test and multiple linear regression used to analyze the relationship between each independent variable with the dependent variable with a significance value <0.05 and the relationship of all independent variables on the dependent variable. The correlation (Pearson correlation test) between energy intake(r=0.397:p=0.000), fat(r=0.396:p=0.000), carbohydrate(r=0.337:p=0.000), and sleep duration(r=0.315:p=0.000) with menstrual duration was significant, whereas for protein intake (Spearman Rank test) was not significantly associated (r=0.018:p=0.841). The value of R2 = 0.252.Based on this, it is important to regulate macro nutrient intake and sleep duration for having normal menstrual duration.